Changing Trends in Teaching Method for Medical Students-Prosection Versus Dissection of Cadavers (Medico Legal Update, 2020)
Background: Cadaveric dissection is considered a tool for studying structural details of the human body.Prosection is demonstrating anatomy of wet specimens preserved and already dissected by experts. Inprosection students get to see multiple wet specimens, museum specimens already dissected by experts andlearn by observing the structures.Methodology: Study is conducted on 30, 1st year MBBS students divided randomly into 2 groups eachhaving 15 students-- Group A and Group B. Informed consent is taken from all the participants prior to thestudy. The second part of study conducted on final year MBBS students on their view on cadaveric dissectionThe anatomy of the neck region which extends over 8 hours of dissection classes are taught to the groupA by traditional dissection demonstration method. The same is taught to Group B by prosection technique.The following day the performance of the students are assessed by a spot identification test consisting of15 questions each of 2 marks pertaining to the specimens as a practical test. In the second part of the studyfeedback is taken in form of a validated questionnaire from final year MBBS students about their view oncadaveric dissection.Results: The performance of the spot identification test conducted on the students was analysed uniformlyand corrected by 2 experts. The results shows the performance of group B (Prosection group) was significantlybetter than group A (p value 0.034 at 95% CI).On analysing the feedback majority of final year studentsliked dissection on cadavers and they felt it promoted group learning and future knowledge on surgicalinstruments and skills.Conclusion: This study suggest that utilizing prosections of the neck region specimens seem to beadvantageous pedagogical approach for teaching Gross Anatomy. Based on the views on cadaveric dissectionof final year studentsit is better toadopt combined approach and expose students to both techniques dissectionand prosection.